Pengaruh Lingkungan Kerja, Motivasi Kerja dan Kepuasan Kerja: Studi Pada Guru SMP Negeri 3 Tangerang Selatan - Siti Mariam; Hari Subagio (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine the impact of work environment (X1), work motivation (X2), and job satisfaction (X3) on teacher performance (Y) at SMP Negeri 3 in South Tangerang City. The study employs a quantitative approach with a survey method, and data were collected through the distribution of questionnaires to 40 teachers. The analysis technique used is multiple linear regression with the assistance of SPSS software version 27 to test the impact of independent variables on the dependent variable. The results indicate that the work environment significantly affects teacher performance, with a regression coefficient of 0.534, meaning that the better the work environment, the higher the teacher's performance. Meanwhile, work motivation (X2) does not have a significant effect on teacher performance, with a low coefficient of 0.184, suggesting that motivation is not the main factor influencing teacher performance at SMP Negeri 3 in South Tangerang City. In contrast, job satisfaction (X3) has a positive and significant impact on teacher performance, with a coefficient of 0.559, indicating that higher job satisfaction leads to better performance. The regression equation obtained is Y = -12.759 + 0.534 X1 + 0.184 X2 + 0.559 X3, which reflects the influence of each factor on teacher performance. Based on these results, it can be concluded that the work environment and job satisfaction are important factors in improving teacher performance, while work motivation does not have a significant impact. Therefore, the school administration should focus more on improving the work environment and enhancing teacher job satisfaction to encourage better performance. This study provides recommendations for school managers to address these two factors in efforts to improve teacher performance.